Magnetic properties and Mössbauer spectroscopy of Fe3O4/CoFe2O4 nanorods - Hähsler, Martin; Landers, Joachim; Nowack, Tim; Salamon, Soma; Zimmermann, Michael; Heißler, Stefan; Wende, Heiko; Behrens, Silke (Inorganic chemistry, 2020)
Fe3O4/CoFe2O4 nanorods were obtained via a simple seed-mediated synthesis. Nanorods were used as seeds to grow CoFe2O4 by thermal codecomposition of the cobalt(II) and iron(III) acetylacetonate precursors. The growth process was monitored by electron microscopy (SEM, TEM), and the resulting nanorods were characterized by powder X-ray diffraction analysis and IR and Raman spectroscopy. Magnetometry and AC susceptometry studies revealed a distribution of Néel relaxation times with an average blocking temperature of 140 K and a high-field magnetization of 42 Am2/kg. Complementarily recorded 57Fe-Mössbauer spectra were consistent with the Fe3O4/CoFe2O4 spinel structure and exhibited considerable signs of spin frustration, which was correlated to the internal and surface structure of the nanorods.